Epigenetic Modifications: Therapeutic Potential in Cancer - Manisha Sachan; Manpreet Kaur (Brazilian Archives of Biology and Technology, 2015)
Epigenetic modifications and alterations in chromatin structure and function contribute to the cumulative changes observed as normal cells undergo malignant transformation. These modifications and enzymes (DNA methyltransferases, histone deacetylases, histone methyltransferases, and demethylases) related to them have been deeply studied to develop new drugs, epigenome-targeted therapies and new diagnostic tools. Epigenetic modifiers aim to restore normal epigenetic modification patterns through the inhibition of epigenetic modifier enzymes. Four of them (azacitidine, decitabine, vorinostat and romidepsin) are approved by the U.S. Food and Drug Administration. This article provides an overview about the known functional roles of epigenetic enzymes in cancer development.